Elevated ambient temperatures and risk of neural tube defects. Issue 5 (22nd November 2016) - Auger, Nathalie; Fraser, William D; Arbour, Laura; Bilodeau-Bertrand, Marianne; Kosatsky, Tom
Abstract : Objectives: The association between ambient heat and neural tube defects has received limited attention, despite imminent climate warming this century. We sought to determine the relationship between elevated outdoor temperatures during neurogenesis and risk of neural tube defects. Methods: We carried out a retrospective cohort study of 887 710 fetuses between 3 and 4 weeks postconception from the months of April through September for 1988–2012 in Quebec, Canada. The exposure was maximum daily temperature and the outcome presence of neural tube defects at delivery. We estimated prevalence ratios (PR) and 95% CIs for the association between maximum temperature and neural tube defects in log-binomial regression models adjusted for maternal characteristics. Results: Relative to 20°C, exposure to temperatures of 30°C was associated with risk of neural tube defects on day 5 (PR 1.56, 95% CI 1.04 to 2.35) and day 6 (PR 1.49, 95% CI 1.00 to 2.21) of the 4th week postconception, during the time of neural tube closure. The trend was apparent for spina bifida and anencephalus/encephalocoele, the main subtypes of neural tube defects. Temperature during the 3rd week postconception was not associated with neural tube defects. Conclusions: Elevated ambient temperatures may be weakly associated with risk of neural tube defects during tube closure.